Response to the Polemic Regarding the Review of Research on Population Losses in the Wola District During the Warsaw Uprising of 1944 - Przeszowski, Kazimierz (Faces of War, 2025)
This response draws attention to the purpose of the original 2024 article, presents general remarks on the polemic text, and discusses the allegations concerning the review of research and the comparative study regarding: The number of victims of mass executions, the size of the German pacification forces, and the area and population of the Wola district. Finally, it addresses the relevance of the findings of the original article in light of the criticisms raised in the polemic.